Bridging the institutional void: An analytical concept to develop valuable cluster services - Tine Schrammel (Management Revue, 2013)
Public policy and cluster management face a common challenge in developing sustainable clusters. Many clusters report difficulties acquiring membership fees once the governmental subsidies come to an end, which brings doubts as to the cluster management's capabilities and likewise to the public policy design. This paper applies the theory of institutional voids and elaborates a theoretical framework to identify cluster services. It shows that analyzing the specific institutional environment of the cluster enables the identification of valuable cluster services. As the identified institutional voids impose a competitive disadvantage on the companies, such services will increase their willingness to pay. Therewith, the article combines cluster literature and institutional theory to draw synergies on participation incentives.
Keywords: D02; I25; O17; J24; L14; L25; L26; P33; 650; cluster services; institutional voids; small and medium sized enterprises; participation incentives; competitive advantage; Regionales Cluster; Institutionelle Infrastruktur; Wettbewerbsvorteil